Atypical Endometrial Hyperplasia, Low-grade: "Much ADO About Nothing". (July 2021) - D'Angelo, Emanuela; Espinosa, Iñigo; Cipriani, Valentina; Szafranska, Justyna; Barbareschi, Mattia; Prat, Jaime
Abstract : Atypical endometrial hyperplasia (AEH) is considered a precursor of endometrioid carcinoma. The 2020 World Health Organization (WHO) classification divides endometrial hyperplasia into 2 categories: hyperplasia without atypia and atypical hyperplasia/endometrioid intraepithelial neoplasia (EIN); however, this classification does not consider the degree of nuclear atypia. We graded nuclear atypia for estimating the risk of finding carcinoma at hysterectomy. Also, we investigated genes involved in endometrial carcinogenesis including mismatch repair (MMR) genes and ARID1A, PIK3CA, PTEN, KRAS, and CTNNB1 . We reviewed 79 biopsies of AEH from 79 patients who underwent hysterectomy within a 1-year interval. Intraobserver and interobserver agreement of grading nuclear atypia and the relationship between the grade of nuclear atypia at biopsy and the findings at hysterectomy were evaluated. Immunohistochemistry for MMR status was performed in all cases and targeted sequencing in 11. Using low-grade versus high-grade nuclear atypia, κ values ranged from 0.74 to 0.91 (89% to 96%) and from 0.72 to 0.81 (87% to 91%) for the intraobserver and the interobserver agreement, respectively. The degree of nuclear atypia at biopsy was highly predictive of the findings at hysterectomy ( P =1.6×10 −15 ). Of 53 patients with low-grade AEH, none had carcinoma at hysterectomy, whereas 6 (6/26; 23%) with high-grade AEH in the biopsy also had high-grade AEH in the uterus and 16 (16/26; 61%) had FIGO grade 1 carcinoma. MMR deficiency was found in 3 of the 79 patients. None of the genes showed a mutational load significantly associated with the degree of nuclear atypia. In summary, our data show high reproducibility within and between observers for the diagnosis of low-grade and high-grade AEH. Most cases of AEH had low-grade nuclear atypia and neither high-grade AEH nor carcinoma was encountered in the corresponding hysterectomy specimens.